Direct Conversion of Aromatic Aldehydes into Benzamides via Oxidation with Potassium Permanganate in Liquid Ammonia - Antoniak, Damian; Sakowicz, Arkadiusz; Loska, Rafał; Mąkosza, Mieczysław (Synlett, 2015)
Oxidation of aromatic aldehydes by KMnO4 in liquid ammonia gives amides directly. The reaction proceeds satisfactorily when the aldehydes are activated by electron-withdrawing substituents on the ring.
Keywords: aldehydes; amides; aminals; oxidation; liquid ammonia